The Utilization of Zn-C Battery Waste and Duck Eggshells in the Synthesis of ZnO/HAp Composite as a Photocatalyst for Methylene Blue Waste Treatment - Ferli Septi Irwansyah; Nafisah Staustan; Eko Prabowo Hadisantoso; Diana Rakhmawati Eddy; Atiek Rostika Noviyanti (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
Synthetic dyes such as methylene blue pose a significant pollution threat due to their chemical stability, resistance to biodegradation, and adverse ecological impacts. Photocatalytic treatment with ZnO is promising; however, particle agglomeration commonly diminishes efficiency. To mitigate this limitation, a ZnO/hydroxyapatite (ZnO/HAp) composite was synthesized from Zn–C battery waste and duck eggshells via a solid-state dispersion method using ZnO: HAp molar ratios of 1:1, 1:3, and 3:1. The materials were characterized by X-ray diffraction (XRD) and scanning electron microscopy (SEM). Photocatalytic activity was assessed by degrading 10 mL of 10 ppm methylene blue with 90 mg of photocatalyst under visible-light irradiation for 180 min. XRD confirmed the successful formation of ZnO, HAp, and ZnO/HAp composites with single-phase zincite and hydroxyapatite structures, crystallite sizes of 14.66–25.09 nm, and crystallinity values of 62.66–86.60%. SEM revealed irregular particle morphologies. All composites were photocatalytically active, achieving methylene-blue decolorization of 96.63%, 91.45%, and 81.07%, with the 1:1 composite exhibiting the highest performance. These results indicate that waste-derived ZnO/HAp composites are promising, low-cost photocatalysts for treating organic dye pollutants.